Influence of Preferences on the Use of Information Resources by the Library and Information Science Undergraduate Students in South-South, Nigeria - Iroroeavwo, Achugbue; Arumuru, Lawrence; Chidi, Ikediashi Anthony; Kusuma, Fauziah Adinda (Department Library of Governance Institut of Home Affairs, 2024)
Background: The use of information resources by the Library and Information Science (LIS) undergraduate students in Delta State, Nigeria, was addressed based on diverse learning preferences, a critical factor potentially influencing academic success. Purpose: This research aimed to explore learning preferences among LIS undergraduate students and assess the influence on the use of information resources. Method: A correlational research design was applied, including 325 students selected through multi-stage sampling from seven state-owned universities in Delta, Edo, and Rivers states. Furthermore, data were collected through questionnaires, with 268 valid responses at an 82% retrieval rate. These were analyzed with descriptive statistics (frequency, percentage, and mean) as well as inferential statistics (Pearson’s product-moment coefficient, and ANOVA), with a criterion mean of 2.50 and an alpha level of 0.05. Result: The results showed that the students had varied learning preferences, including verbal presentations (68%), physical interaction with materials (66%), and watching educational videos (64%). Preferences significantly influenced the use of information resources (Agg. x̄ = 2.83), with a positive correlation between these two variables (r = .907, p < 0.05). Additionally, a significant difference was observed between the education level of students and learning preferences (F = 2,265 = 1189.172, p < 0.05). Conclusion: The students were found to benefit majorly from the combination of traditional and modern teaching methods. Mutual collaboration between university librarians and coordinators of information resources with the faculty was recommended to ensure the correspondence of educational materials to learning preferences.